Frank Wood's business accounting 2 - Wood, Frank, Omuya, J.O.; Omuya, J.O (England : Longman, 1983)
This is the second volume of the textbook, it completes the coverage for the West African Examination Council GCE, 'A' level papers in Accounting, so far as the financial accounting aspect is concerned.
Includes index.
jbi 12/03/2018
Loans
Keywords: Accounting